Impact of building geometry factors on thermal comfort and energy performances of glass façade high-rise office buildings in hot and humid climate Malaysia - Roslan, Nurul Hidayah (2022)
Limited land in cities have caused an increase of high-rise buildings and caused changes in the morphology and microclimate. Besides, the application of full glass façade on high-rise buildings has become a trend and could influence the building energy and thermal comfort in hot and humid climate. Thus a study was conducted to evaluate the variations of performance at different building heights, the effect of building depth and building shape on building energy and long-term thermal comfort performances. A base case model of 20-storey high-rise building with a full glass façade was simulated using the EnergyPlus and RStudio programmes. A total of 4 microclimate conditions, 6 building depth ratios, and 8 building shapes were evaluated by manipulating the orientations and floor areas of the building. The results indicated that there is a reduction in the building energy use after considering the effect of microclimate along with the building height. The deep building (1:1) was found to perform better than the narrow building (6:1). For building shapes, circle shape is the most energy efficient shape, while Y-shape has the lowest energy performance. In conclusion, the application of a full glass façade shows more influence on the thermal comfort performance compared to building energy. Hence, the application of a full glass façade in the hot and humid climate is less favourable and requires consideration of appropriate building geometries at the early design stage